Determinants Related to Interest of Women of Childbearing Age in the Visual Inspection of Acetic Acid (IVA) - Julianti, Neneng (Universitas Islam Lamongan, 2022)
Â Based on Riskesdas 2018 data, the prevalence of tumors/cancer in Indonesia shows an increase from 2013 to 1.79 per 1000 population in 2018. The highest prevalence of cancer isYogyakarta at 4.86 per 1000 population, followed by West Sumatra at 2.47 per 1000 population and Gorontalo2.44 per 1000 population. From the recapitulation in West Java, the early detection of cervical cancer (IVA), in 2018 it decreased by 43,267. The coverage of the examination was 3.02 per 100,000 residents, the results of the examination showed 4,183 positive IVA, 263 Suspicious Ca cervix. From the results of the preliminary study, 30 WUS who have carried out the IVA 1 WUS & 29 WUS examination have not been examined for IVA, then 10 WUS who are interested in doing IVA and 20 WUS who are not interested in doing IVA. The purpose of the study is to determine the factors related to the interest of Women of Childbearing Age (WUS) in the Visual Inspection examination of Acetic Acid ( IVA) in Bantarjaya Village, Kec Pebayuran Kab Bekasi in 2021. The method used in this study is quantified analytics with a cross-sectional approach and sampling using purposive sampling techniques. With a population of 270 women of childbearing age and a sample of 178 sempel. Data collection uses questionnaires. The results of the analysis through Univariate, Bivariate & Multivariate. The results of the Bivariate analysis used the chi-square test with a meaningfulness level of 95% (Î± = 0.05 and showed that there was a relationship between the education of women of childbearing age (P Value = 0.000), Knowledge (P Value = 0.018), Husband Support (P Value = 0.035), Health Workers Support (P Value = 0.020), and The Interest of Women of Childbearing Age in the Examination of Acetic Acid Visual Inspection (IVA). Then the multivariate results there are dominant factors, namely the Education variable, namely ( P Value 0.000 & OR 3,714) to WUS Interest in The Acetic Acid Visual Inspection Examination (IVA) in Bantarjaya Village, Pebayuran District, Bekasi Regency in 2021. The conclusion is that there is a relationship between Education, Knowledge, Husband Support, Support of Health Workers with the Interest of Women of Childbearing Age in the Acetic Acid Visual Inspection Examination (IVA) in Bantarjaya Village, Pebayuran District, Bekasi Regency in 2021. The suggestion with this study is that it is hoped that the achievement of the IVA examination as an early detection of cervical cancer can be achieved.